CULTURE-BASED SCHOOL LEADERSHIP IN IMPROVING THE QUALITY OF THE INTEGRATED ISLAMIC JUNIOR HIGH SCHOOL OF THE TARBIYAH ISLAMIYAH EDUCATION FOUNDATION IN LUBUK CEMARA - Mahasa, Rifqi; Syakdiah, Halimatun; Irwansyah (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study explores the multifaceted relationship between school principal leadership and school quality improvement at SMP integrated Islam Islamic Tarbiyah Education Foundation Lubuk Cemara School.  Employing a phenomenological approach, this research investigates the lived experiences of teachers and staff to understand how the principal’s leadership style, particularly as it relates to fostering a positive work culture, impacts various aspects of school quality. Data was collected through in-depth semi-structured interviews and document analysis, focusing on themes related to leadership practices, teacher morale, instructional strategies, and student outcomes.  The findings reveal nuanced insights into the ways in which the principal’s leadership, both directly and indirectly, shapes the school environment and contributes to overall school effectiveness.  The study contributes to a richer understanding of the complex interplay between leadership, work culture, and school quality, offering valuable implications for school improvement initiatives at SMP integrated Islam Islamic Tarbiyah Education Foundation Lubuk Cemara School  and similar institutions